Effective Realization of Social Partnership and Supply Chain Management in the Russian Federation Economy - Oksana Anatolevna Ignateva; Askar Nailevich Mustafin; Margarita Nikolaevna Maksimova (International Journal of Supply Chain Management, 2019)
Abstract-This article is devoted to studying of social partnership and supply chain strategy from the point of view of its role and value for the economy of the Russian Federation. The group of authors carried out the analysis of the category "social partnership" and also features of its functioning at the present stage of development of the domestic economy. Social partnership is the necessary instrument of regulation of the market economy, and, at its competent organization serves as a very powerful regulator of social and labor disputes. At a stage of formation of the Russian economy, such economic event as "social partnership" still was insufficiently created according to "new market conditions" and therefore cannot fulfill fully the purpose and function effectively. Here both the feature of "tripartizm", and the existence of the internal social conflict, and not readiness of such subject takes place as businessmen (business in general) fully to fulfill the social obligations to society and workers, being built in process of social partnership as the active participant. At the same time, the state, in turn, does not create due conditions to motivate business more actively to participate in processes of creation of effective cooperation between authorities, businessmen and workers, creating the last incentives for more productive and productive work for the benefit of society and the country.